Case Report: Cariprazine Efficacy in Young Patients Diagnosed With Schizophrenia With Predominantly Negative Symptoms - Vasiliu, Octavian (Frontiers in Psychiatry, 2021)
Negative symptoms of schizophrenia are among the most invalidating clinical manifestations of this disorder, and they are correlated with poorer prognosis, lower quality of life, and fewer chances for successful social reintegration and professional rehabilitation. Although atypical antipsychotics have been associated with higher efficacy on negative symptoms than typical agents, not all of them are equally effective. Cariprazine is a new D3 and D2 receptor partial agonist, and its high D3 affinity may be useful for decreasing several adverse events (e.g., extrapyramidal symptoms or hyperprolactinemia), and also for increasing this drug's efficacy over negative symptoms. This case series presents 3 young adults with predominantly negative symptoms during treatment with an atypical antipsychotic, administered in stable dose within the therapeutic range, and for at least 4 weeks prior to the cariprazine switch. These patients (two male and one female, mean age 35.7 years) were diagnosed with schizophrenia, according to the DSM-5 criteria. They were evaluated using Positive and Negative Syndrome Scale (PANSS), Clinical Global Impression-Severity (CGI-S), and Global Assessment of Functioning (GAF). Their mean initial values were 80.3 on PANSS, 4.3 on CGI-S, and 48 on GAF. All these patients were already on a treatment with stable doses of atypical antipsychotics (olanzapine 10 mg/day, n=1, risperidone 6 mg/day, n=1, and quetiapine 600 mg/day, n=1). Cross-titration to cariprazine was initiated, from 1.5 mg qd up to 6 mg qd, during a mean period of 2.7 weeks. After 12 weeks of cariprazine 6 mg/day, the positive scale of PANSS was relatively stable compared to baseline, while the negative mean score decreased by 22%. Also, the mean CGI-S improvement was 15.4% and the GAF mean score increased by 17%. The overall tolerability was good, without severe adverse events being reported. Conclusions: Cariprazine is well tolerated and efficient for patients diagnosed with schizophrenia who have significant negative symptoms that impair daily functioning. After 12 weeks cariprazine succeeded in improving negative symptoms, global functioning, and clinical global impression.